Dynamic responses of laminated composite sandwich beam with double-viscoelastic core layers. (2021) - Selvaraj, Rajeshkumar; Subramani, Mageshwaran; More, Gaurav; Ramamoorthy, Manoharan
Abstract: In this paper, the dynamic responses of double-core sandwich composite beam has been performed using experimental and numerical methods. The numerical model of the laminated composite single-core and double-core sandwich beams has been modelled using ANSYS software. An experimental modal test has been carried for single-core and double-core sandwich beams under clamped clamped (CC) and clamped free (CF) end conditions. The developed single-core and double-core numerical model is verified with experimental results. The analysis results clearly shows that the stiffness of the double-core composite sandwich beam are higher than those of single-core composite sandwich beam due to the higher stiffness offered by double-core. Further, the parametric study was performed to analyze the effect on a laminated composite double-core sandwich beam of different fiber angle orientation, thickness ratios and aspect ratios.